KNOWLEDGE TRANSFER IN SELECTED EUROPEAN UNIVERSITIES - Malinen, Pasi; Sinervo, Petteri (European Scientific Journal, ESJ, 2015)
To exploit the research results commercially or otherwise has become increasingly important for universities. When pursuing this, universities have established Technology Transfer Offices and developing links to industries and businesses. This paper focuses on the ways selected European universities have established and organised their Technology Transfer (TT) activities. The study was made using the model developed by professor Allan Gibb as a framework. The data collection work was done in a series of interviews in four European universities. The background material and data was collected from public sources, mainly from the universities’ web pages. The study recognised certain elements, which affect the success of the TT activities. Technology Transfer operation requires top management support and a link to university’s strategy. The size of the economic area and the amount of cumulative research results are important factors in TT. Successful Technology Transfer can be organised centralised or decentralised way as long as the operating model is known to all involved parties. Creating an entrepreneurial atmosphere and showing that the university values the exploitation of the research results appears to be highly important in order get results from TT activities.